Clinical features and characteristics of pediatric patients with COVID-19 infection: Experiences in a Tertiary Taiwan Hospital. Issue 35 (2nd September 2022) - Bai, Geng-Hao; Shih, Ping-Yi; Chen, Shih-Yen; Hsieh, Kai-Sheng; Chou, Cheng-Che; Feng, Po-Hao; Kong, Shu-Sing; Lin, Wen-Chuan; Lu, Meng-Che
Abstract : Coronavirus disease 2019 (COVID-19) patients have distinct clinical features in the pediatric groups. However, there is a paucity of research focused on clinical manifestation within pediatric group in Taiwan. This study is to conduct a retrospective study of the clinical features of COVID-19 in Taiwan pediatric patients. A retrospective study was conducted on pediatric patients (Aged ≤ 18 years) in a Northern Taiwan hospital from May 1st, 2021 to June 30th, 2021. Thirty-eight patients were included from emergency room. They were laboratory confirmed COVID-19 through specimens from nasopharyngeal swab by real-time reverse-transcription polymerase chain reaction (RT-PCR). Data including RT-PCR cycle threshold (Ct) values, clinical and epidemiological features were collected and analyzed. Thirty-eight patients aged from 7-month to 18-year-old were included. The median age of patients was 15-year-old. The patients had sex ratio of 23 males to 15 females. More than half patients were infected from family members. Asymptomatic patients were 47.37%. In the symptomatic patients, fever (34.21%) was the most predominant symptom. Cough, nasal obstruction and sore throat were also common. Asymptomatic children had significantly higher Ct-values than symptomatic children, and diagnosed patients with Ct-values more than 19 were associated with asymptomatic infection ( P = .0084). Ct-values higher than 19 were associated with asymptomatic infection, which may be a predictor of pediatric disease severity. Our results highlight the distinct clinical manifestations and outcomes in pediatric COVID-19 patients. Compared to the adults, pediatric patients aged ≤ 18 years with COVID-19 in Taiwan mainly had mild disease.